Quantification Of Dense Nonaqueous Phase Liquid Saturation In Double-Porosity Soil Media Using A Light Transmission Visualization Technique - Alazaiza, M. Y. D.; Ngien, S. K.; Bob, M. M.; Samira A., Kamaruddin; Wan Faizal, Wan Ishak (Begell House Inc., 2017)
In this research, the light transmission visualization (LTV) technique was used to measure the dense nonaqueous phase liquid (DNAPL) saturation distribution in a two-dimensional (2-D) flow chamber packed with double-porosity soil medium. This, to the best of our knowledge, is a new application of LTV in measuring DNAPL saturation as well as monitoring its migration in double-porosity soil media. The double-porosity structure was created using layers of fine silica sand and solidified kaolin clay spheres. Tetrachloroethylene (PCE) was used to simulate DNAPL and was dyed with Oil-Red-O for better visualization. Known amounts of PCE were injected into the flow chamber before being correlated to amounts calculated using image analysis based on the LTV method. A strong correlation having an R2 value of 0.994 was found between the injected PCE volumes and calculated PCE volumes obtained from the LTV method. For comparative purposes, the same experiment was carried out by filling the flow chamber with local silica sand as a single-porosity medium to investigate the influence of soil structure on DNAPL migration. Results, again, showed a strong correlation, with an R2 value of 0.996, between the amounts of PCE injected into the flow chamber and the calculated amounts of PCE. A significant difference in the migration of PCE in the two experiments was observed as the rate of PCE migration in the double-porosity medium was much faster compared to the migration rate in the single-porosity medium. This finding is most likely due to the occurrence of interaggregate pores in the double-porosity soil. This research proves that the noninvasive and nonintrusive LTV technique can be used to quantify DNAPL saturation in double-porosity soil structure in 2-D, two-phase systems.